2016
DOI: 10.1128/iai.01171-15
|View full text |Cite
|
Sign up to set email alerts
|

The Chromosome-Encoded Hypothetical Protein TC0668 Is an Upper Genital Tract Pathogenicity Factor of Chlamydia muridarum

Abstract: cWe previously associated a missense mutation of the tc0668 gene of serial in vitro-passaged Chlamydia muridarum, a murine model of human urogenital C. trachomatis, with severely attenuated disease development in the upper genital tract of female mice. Since these mutants also contained a TC0237 Q117E missense mutation that enhances their in vitro infectivity, an effort was made here to isolate and characterize a tc0668 single mutant to determine its individual contribution to urogenital pathogenicity. Detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
86
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 37 publications
3
86
0
Order By: Relevance
“…2). We found that both wild-type and mutant C. muridarum displayed similar courses of live-organism shedding from the lower genital tract regardless of their genotypes, confirming previous findings (15). However, all of our C. muridarum mutants…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…2). We found that both wild-type and mutant C. muridarum displayed similar courses of live-organism shedding from the lower genital tract regardless of their genotypes, confirming previous findings (15). However, all of our C. muridarum mutants…”
Section: Resultssupporting
confidence: 77%
“…muridarum mutants that fail to induce hydrosalpinx are defective in spreading to the GI tract following intravaginal inoculation. We previously reported that a series of C. muridarum mutants were highly attenuated in induction of hydrosalpinx in the mouse upper genital tract (14,15). However, the mechanisms of attenuation remained unknown.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because a single inoculation of C. muridarum organisms in the mouse lower genital tract can cause hydrosalpinx and infertility (7)(8)(9), closely mimicking the tubal adhesion, hydrosalpinx, and infertility observed in women urogenitally infected with C. trachomatis (10)(11)(12). Although C. muridarum is not a natural sexually transmitted agent of mice, chlamydiologists have used this model not only to identify both chlamydial (13)(14)(15)(16)(17) and host (1,5,(18)(19)(20)(21)(22)(23)(24) pathogenic determinants but also to define the roles of ascending infection and tubal inflammation in chlamydial induction of hydrosalpinx (9,16,25,26). Nevertheless, questions such as how a self-limited infection with C. muridarum in the mouse genital tract can trigger tubal fibrosis or hydrosalpinx that lasts long after the tubal infection is resolved (9,25) remain unanswered.…”
mentioning
confidence: 99%